Clinical impact of FLT3 mutation load in acute promyelocytic leukemia with t(15;17)/PML-RARA - Susanne Schnittger; Ulrike Bacher; Claudia Haferlach; Wolfgang Kern; Tamara Alpermann; Torsten Haferlach (Haematologica, 2011)
Background Combined treatment with all-trans-retinoic acid and chemotherapy is extremely efficient in patients with acute promyelocytic leukemia with t(15;17)/PML-RARA, but up to 15% of patients relapse.Design and Methods To further clarify the prognostic impact of parameters such as FLT3 mutations, we comprehensively characterized the relation between genetic features and outcome in 147 patients (aged 19.7–86.3 years) with acute promyelocytic leukemia.Results Internal tandem duplications of the FLT3 gene (FLT3-ITD) were detected in 47/147 (32.0%) and tyrosine kinase domain mutations (FLT3-TKD) in 19/147 (12.9%) patients. FLT3-ITD or FLT3-TKD mutation status did not have a significant prognostic impact, whereas FLT3-ITD mutation load, as defined by a mutation/wild-type ratio of less than 0.5 was associated with trends to a better 2-year overall survival rate (86.7% versus 72.7%; P=0.075) and 2-year event-free survival rate (84.5% versus 62.1%, P=0.023) compared to the survival rates of patients with a ratio of 0.5 or more. Besides the t(15;17), an additional chromosomal abnormality was detected in 57 of 147 cases and did not show a significant impact on survival. White blood cell counts of 10×109/L or less versus more than 10×109/L were associated with a better 2-year overall survival rate (88.3% versus 69.4%, respectively; P=0.015), as was male sex (P=0.040). In multivariate analysis, only higher age had a significant adverse impact.Conclusions Prospective trials should further investigate the clinical impact of the FLT3-ITD/wild-type mutation load aiming to evaluate whether this parameter might be included in risk stratification in patients with acute promyelocytic leukemia.